2017
DOI: 10.1016/j.jcyt.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Low interleukin-2 concentration favors generation of early memory T cells over effector phenotypes during chimeric antigen receptor T-cell expansion

Abstract: Background. Adoptive T-cell therapy offers new options for cancer treatment. Clinical results suggest that T-cell persistence, depending on T-cell memory, improves efficacy. The use of interleukin (IL)-2 for in vitro T-cell expansion is not straightforward because it drives effector T-cell differentiation but does not promote the formation of T-cell memory. We have developed a cost-effective expansion protocol for chimeric antigen receptor (CAR) T cells with an early memory phenotype. Methods. Lymphocytes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…However, along with induction of potent anti-tumor T cells, IL-2 is also known to cause Activation Induced Cell Death (AICD) and differentiation into immunosuppressive regulatory T cells (62). Hence, low dose IL-2 in CAR T cell therapy has been suggested for achieving better anti-tumor responses and to overcome the immunosuppressive effects of IL-2 (63).…”
Section: Introductionmentioning
confidence: 99%
“…However, along with induction of potent anti-tumor T cells, IL-2 is also known to cause Activation Induced Cell Death (AICD) and differentiation into immunosuppressive regulatory T cells (62). Hence, low dose IL-2 in CAR T cell therapy has been suggested for achieving better anti-tumor responses and to overcome the immunosuppressive effects of IL-2 (63).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a rest period could also reinvigorate mitochondrial metabolism to sustain long-term T cell persistence and function. It should also be considered that in vitro generation and amplification of tumor-infiltrating lymphocytes for adoptive cell transfer or CAR T cells often require incubation in supraphysiologic concentrations of nutrients such as glucose, or cytokines like IL-2 ( 164 ). Based on preclinical observations ( 7 , 30 , 165 ), a transient preincubation in a more physiologic medium inducing glucose restriction or treatment with rapamycin (or analogs) is a promising strategy to prime T cells for Tm cell differentiation ( 161 , 164 , 166 , 167 ).…”
Section: Overcoming Metabolic Competition In the Tumor Microenvironment To Improve Tm Cellsmentioning
confidence: 99%
“…It should also be considered that in vitro generation and amplification of tumor-infiltrating lymphocytes for adoptive cell transfer or CAR T cells often require incubation in supraphysiologic concentrations of nutrients such as glucose, or cytokines like IL-2 ( 164 ). Based on preclinical observations ( 7 , 30 , 165 ), a transient preincubation in a more physiologic medium inducing glucose restriction or treatment with rapamycin (or analogs) is a promising strategy to prime T cells for Tm cell differentiation ( 161 , 164 , 166 , 167 ). Along the same line, the treatment of CD8 + T cells with the engineered IL-2 partial agonist H9T improves mitochondrial fitness and promotes a stem cell–like state ( 168 ).…”
Section: Overcoming Metabolic Competition In the Tumor Microenvironment To Improve Tm Cellsmentioning
confidence: 99%
“…It has been reported that low concentration of IL-2 favored the generation of memory precursors. 16 The slow and controlled release of IL-2/Fc from NG backpacks resulted in a low effective concentration of IL-2/Fc around T-cells and thus drove the memory formation. Moreover, T-cells backpacked with IL-2/Fc NGs showed 7.8-fold lower frequency of PD-1 + LAG-3 + exhaustion phenotype (Fig.…”
Section: Il-2/fc Ng Backpacks Expand T-cells In Vitro With Increased mentioning
confidence: 99%